Variability of terms in translation studies: problems of term use and analysis of translation decisions (an experimental and methodological study) - Dorofeieva, Marharyta (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
The article deals with the terminological variability in translation studies as a factor influencing the research methodology and practical translation analysis in students’ scientific and qualification works. The relevance of the study is determined by the concepts with unstable definitions and variable nomination in the translation studies´ terminological system. It is important to specify the extension and the intension of the translation studies´ concepts as well, in order to ensure the correctness of the chosen theoretical and methodological basis and further practical translation analysis. The aim of the study was to identify the relationship between the variable terms in translation studies, the peculiarities of their use and the practical analysis of translation in students’ works. A heuristic hypothesis was put forward and an experimental and methodological study was conducted with the participation of master’s students based on the tasks in a Google class on the discipline ‘Methodological Foundations of Translation Research’.The variability of terms in translation studies has a negative impact on translation analysis procedures and the methodological validity in students’ scientific and qualification works. There is a correlation between unconscious use of variable terms, revealed in the inaccurate definitions of the ‘equivalence’ and ‘adequacy’ concepts on the one hand, and defects in the further practical analysis by the participants on the other hand. For the correct use of terminology and translation analysis it is recommended to choose a specific translation studies’ paradigm as the basis for the research methodology and the consistent use of terminology within the chosen paradigm.